A Multistep Approach to Deal With Advanced Heart Failure: A Case Report on the Positive Effect of Cardiac Contractility Modulation Therapy on Pulmonary Pressure Measured by CardioMEMS - Visco, Valeria; Esposito, Cristina; Manzo, Michele; Fiorentino, Antonio; Galasso, Gennaro; Vecchione, Carmine; Ciccarelli, Michele (Frontiers in Cardiovascular Medicine, 2022)
During the last years, the management of heart failure (HF) made substantial progress, focusing on device-based therapies to meet the demands of this complex syndrome. In this case report, we present a multistep approach to deal with HF. Specifically, we report the first patient subjected to both Optimizer Smart® (Impulse Dynamics Inc., Marlton NJ, USA) and CardioMEMS devices implantation. A 72-year-old male with HF and reduced ejection fraction was admitted to our cardiology department in January 2021, following a progressive shortening of the time between hospitalizations for levosimendan infusions. Specifically, the patient was monitored daily by CardioMEMS, and a strategy of levosimendan infusions guided by the device had been adopted. He was also a carrier of MitraClips and CRT-D, and had optimized HF medical therapy. In January 2021, the patient implanted Optimizer Smart® device for cardiac contractility modulation (CCM) therapy because of poor response to therapy and elevated pulmonary artery pressure (PAP). CCM significantly reduced PAP values following discharge (PAPs 33.67 ±2.92 vs 40.6±3.37 mmHg, PAPd 14.5±2.01 vs 22.5±2.53 mmHg, PAPm 22.87±2.20 vs 30.9±2.99 mmHg, HR 60.93±1.53 vs 80.83±3.66 bpm; p<0.0001), with persisting effect at 9 months. The usefulness of CCM is objectively demonstrated for the first time by continuous invasive monitoring of PAP by CardioMEMS, which can suggest the correct timing for CCM implantation.